2020
DOI: 10.2478/eko-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

Land Cover and Land Use Change-Driven Dynamics of Soil Organic Carbon in North-East Slovakian Croplands and Grasslands Between 1970 and 2013

Abstract: AbstractSoil organic carbon (SOC) in agricultural land forms part of the global terrestrial carbon cycle and it affects atmospheric carbon dioxide balance. SOC is sensitive to local agricultural management practices that sum up into regional SOC storage dynamics. Understanding regional carbon emission and sequestration trends is, therefore, important in formulating and implementing climate change adaptation and mitigation policies. In this study, the estimation of SOC stock and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In contrast, losses take place mainly in the initial 25-year period (Figure 7). Koso et al [33] and Skalsky et al [34] found that the application of RothC for modeling SOC stock in 1970-2020 for different regions of Slovakia would require detailed information on where the land cover changes occurred both in space and time, as it had a strong effect on the SOC stock temporal dynamics. However, in a study of the spatial evolution of topsoil SOC driven by climate change and land use change for France up to the year 2100, Meersmans et al [35] concluded that climate change would have a much more significant influence on future SOC losses in mid-latitude mineral soils than land use change dynamics.…”
Section: The Importance Of the Land Use Historymentioning
confidence: 99%
“…In contrast, losses take place mainly in the initial 25-year period (Figure 7). Koso et al [33] and Skalsky et al [34] found that the application of RothC for modeling SOC stock in 1970-2020 for different regions of Slovakia would require detailed information on where the land cover changes occurred both in space and time, as it had a strong effect on the SOC stock temporal dynamics. However, in a study of the spatial evolution of topsoil SOC driven by climate change and land use change for France up to the year 2100, Meersmans et al [35] concluded that climate change would have a much more significant influence on future SOC losses in mid-latitude mineral soils than land use change dynamics.…”
Section: The Importance Of the Land Use Historymentioning
confidence: 99%
“…In contrast, losses take place mainly in the initial 25 year period (Fig.2). Koso et al [27] and Skalsky et al [28] found that application RothC for modelling SOC stock in 1970-2020 for different regions of Slovakia would require detailed information on where land cover changes occurred both in the space and time, as it has a strong effect on SOC stock temporal dynamics. However, in a study of the spatial evolution of topsoil SOC driven by climate change and land use change for France up to the year 2100 Meersmans et al [29] concluded that climate change would have a much more significant influence on future SOC losses in mid-latitude mineral soils than land use change dynamics.…”
Section: The Importance Of the Land Use Historymentioning
confidence: 99%
“…The potential to manage soil for climate change mitigation is also bound to a local context, where the SOC dynamics under different land uses depend on complex interactions between climate, vegetation, soil biota, soil fauna, soil properties, and topography (Wiesmeier et al, 2019). This further complicates the estimation of the mitigation potential of converted soils, and points to the need to incorporate well-founded local knowledge when designing mitigation measures (Skalský et al, 2020). This motivates studies investigating how SOC stocks vary in soils converted from croplands to grasslands with low-intensity grazing (hereafter grazed grassland, see Bengtsson et al (2019) for definition) on a local scale and through time.…”
Section: Introductionmentioning
confidence: 99%